Grading model for Singapore charities. - Liang, Yiwen. (2008)
This report considers notion of accountability and governance in the charitable sector. It is an exploratory study which looks into the grading models used by overseas independent watchdogs and uses them as a basis to develop a grading system for charities in Singapore. A two-pronged approach was adopted in the grading system consisting of financial and non-financial grading aspects. The financial aspect of the grading system uses ratio to evaluate the efficiency of charities while the non-financial aspect of the grading system evaluates the transparency of the charities.